SOCIALIZATION OF THE IMPORTANCE OF SPORT IN MAINTAINING HEALTH AND FITNESS IN THE TIME OF COVID-19, THE COMMUNITY OF TOPANG VILLAGE MERANTI ISLANDS DISTRICT: SOCIALIZATION OF THE IMPORTANCE OF SPORT IN MAINTAINING HEALTH AND FITNESS IN THE TIME OF COVID-19, THE COMMUNITY OF TOPANG VILLAGE MERANTI ISLANDS DISTRICT - Kamarudin (Community Education Engagement Journal, 2021)
This community service activity aims to provide knowledge to the community about the importance of the role of sports in maintaining health and fitness during the Covid-19 pandemic, the people of Topang Village, Meranti Islands Regency. This community service activity was carried out in Topang Village, Meranti Islands Regency. Participants who took part were the community and youth in Topang Village, Rangsang Subdistrict, Meranti Islands Regency, who attended were 34 people. The method of implementation in community service activities in Topang Village, Rangsang Subdistrict, Meranti Islands Regency, includes: (1) Preparation Stage. The preparatory stage carried out includes: surveying the location, consolidating and determining the location and target, the preparation of service materials / materials, which include: the importance of a healthy life, getting used to exercise, always obeying health protocols (2) Community Service Implementation Phase. The stages in the implementation of the service are carried out to prepare, among others: Explanation of the importance of the role of sports in maintaining health and fitness during the pandemic era-19. The expected outputs in this community service activity are: (1) Cultivate the ability of the community to maintain health and fitness during the Covid-19 pandemic. (2) Publication in Community Service Journal. Keywords : Sports, health, pandemic